Disturbed Copper Bioavailability in Alzheimer's Disease. (15th November 2011) - Kaden, Daniela; Bush, Ashley I.; Danzeisen, Ruth; Bayer, Thomas A.; Multhaup, Gerd
Abstract : Recent data from in vitro, animal, and human studies have shed new light on the positive roles of copper in many aspects of AD. Copper promotes the non-amyloidogenic processing of APP and thereby lowers the A β production in cell culture systems, and it increases lifetime and decreases soluble amyloid production in APP transgenic mice. In a clinical trial with Alzheimer patients, the decline of A β levels in CSF, which is a diagnostic marker, is diminished in the verum group (8 mg copper/day), indicating a beneficial effect of the copper treatment. These observations are in line with the benefit of treatment with compounds aimed at normalizing metal levels in the brain, such as PBT2. The data reviewed here demonstrate that there is an apparent disturbance in metal homeostasis in AD. More research is urgently needed to understand how this disturbance can be addressed therapeutically.